Price decisions and employment equilibrium - Encarnacion, Jose, Jr (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1988)
Instead of expected profit maximization, this paper assumes a safety-first objective so that the firm will set a higher price for its product if cost or demand is higher, which has macroeconomic implications. With all firms in the economy as price setters, there is an equilibrium of prices which entails as employment equilibrium with inflation, and allows for procyclical real wages.